Informal land markets and ethnic kinship in West African cities - (:unkn) unknown (My University, 2024)
We present an urban land use model with land tenure insecurity and information asymmetry regarding risks of contested land ownership, a very common issue in West African cities. A market failure emerges as sellers do not internalize the impact of their market participation decision on the average quality of traded plots, which in turn affects other sellers and buyers' decisions. The equilibrium is suboptimal and has too many transactions of insecure plots and too few transactions of secure plots. This market failure can be addressed when agents trade along trusted kinship lines that discourage undisclosed sales of insecure plots. Such kinship matching is an important feature of West African societies, including on the market for informal land, as illustrated by a unique survey administered in Bamako, Mali. In the model, the extent to which the market failure is addressed increases with the intensity of kinship ties. When sellers also have the possibility of registering their property right in a cadastre, this not only further attenuates information asymmetry but also helps reduce risk. We find complementarity between kinship matching and registration: As transactions along trusted kinship lines tend to involve plots that are more secure on average, kinship matching makes registration better targeted at insecure plots traded outside kinship ties. In this context, a partial registration fee subsidy can bring the economy to the social optimum.
Keywords: African Research